Inequality and Fiscal Policy (GESTIÓN Y TENDENCIAS, 2020)
In these times, characterized by a widespread increase in inequality, this article reviews the existing literature on the role fiscal policy can play in reducing it. We begin with the most relevant general findings, continue with the redistributive capacity of the different fiscal instruments, and conclude with the redistributive effects of fiscal consolidation.